SIGNIFICANCE OF NBTA AS AN INDICATOR OF GEOCHEMICAL PROCESSES IN THE CRUST-MANTLE SYSTEM - Green T.H. (My University, 1995)
A mantle value of # 17.5 for NbTa appears well established; less well established are crustal values of # 11-12, although it appears that NbTa for crustal-derived melts is less than mantle NbTa, demonstrating fractionation of these two elements during crustal evolution, and suggesting that NbTa variation may be indicative of a particular chemical process within the crust-mantle system.Experimental studies on silicate and carbonatitic liquids at high pressure indicate that, although silicate minerals such as garnet, amphibole and clinopyroxene do fractionate Nb and Ta, the partition coefficients (D's) for both elements are very low. Thus involvement of these minerals may explain relatively small changes in NbTa, but appears inadequate to explain the crust-mantle variation. However, high-quality data for Nb, Ta may be used to provide information on mantle melting or metasomatic processes (e.g., amphibole in the source region decreasesNbTa in derived melts, while carbonatitic metasomatism will increase NbTa in affected mantle). Titanate minerals have high D's for Nb and Ta, and do fractionate these elements (e.g., DNbDTa rutile/liquid of 0.5-0.8), and their involvement in crystal fractionation would increase NbTa in derivative liquids. In contrast,DNbDTa for rutile/fluid is # 1.25, so that rocks affected by fluid equilibrated with residual rutile will show a decrease in NbTa.Some Archaean gneisses appear to have high NbTa, and may be a complementary component to that part of the crust which has a relatively low NbTa, such as crustal-derived magmas (e.g., A- and I-type granites and silicic volcanics). Within the crustal system pegmatites are known to have extremely high and variable Nb, Ta contents, often with low NbTa. A fluid is generally considered to be involved in the generation of these rocks. Thus it is possible that fluid/melt partitioning may be the key to fractionating Nb and Ta, with preference for Ta in the fluid, and enrichment of Ta relative to Nb into the mid-upper crustal system, as the crust evolved, through upward movement of fluid.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей